The Interwar Japanese Intelligence Activities in the Baltic States: 1918-1940 - Shingo Masunaga (Estonian Academy of Sciences and the Institute for History, Archelogy, and Art History of Tallinn University, 2022)
This article aims to unveil the truths of the interwar Japanese intelligence activities in the Baltic States. Starting from the publication of Yuriko Onodera’s memoir ‘In the Shore of the Baltic Sea’ in 1985, the activities began to catch scholarly attentions. The activities were partially covered in some of the previous academic publications, such as a general picture of Japanese intelligence plan ‘1932’ in Kuromiya & Mamoulia (2016). However, this is the first-ever article to provide a perspective of the activities of the Japanese military attaché office in Riga.